PENGARUH ORIENTASI KEWIRAUSAHAAN, ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP KINERJA PEMASARAN (STUDI PADA PARA PENGUSAHA PENGOLAH KOPI TOLAKI DI KABUPATEN KONAWE SELATAN) - Hasnawati Hasnawati; Endro Sukotjo; Yusuf Yusuf; Isalman Isalman (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2022)
The aims of this study were to determine and analyze: (1) The effect of entrepreneurial orientation, market orientation, and product innovation on marketing performance of tolaki coffee processing entrepreneur South Konawe Regency, (2) The effect of entrepreneurial orientation on marketing performance of tolaki coffee processing entrepreneur South Konawe Regency, (3) The effect of market orientation on marketing performance of tolaki coffee processing entrepreneur South Konawe Regency, (4) The effect of product innovation on marketing performance of tolaki coffee processing entrepreneur South Konawe Regency. The number of samples in this study was all entrepeneur of Coffe Tolaki at South Konawe Regency about 34 respondents. The analysis technique was using multiple regression analysis with SPSS 25.The results showed that: (1) entrepreneurial orientation, market orientation, and product innovation has a positive and significant effect on marketing performance of tolaki coffee processing entrepreneur South Konawe Regency, (2) Entrepreneurial orientation has a positive and significant effect on marketing performance of Tolaki coffee processing entrepreneur South Konawe Regency, (3) Market orientation has a positive and significant effect on marketing performance of Tolaki coffee processing entrepreneur South Konawe Regency, (4) Product innovation has a positive and significant effect on marketing performance of Tolaki coffee processing entrepreneur South Konawe Regency